THE RELATIONSHIP OF EXCLUSIVE ASKING WITH STUNTING IN CHILDREN AGED 3-5 YEARS - Utami, Wiwik; Susanti, Dwi Agung; Azizah, Amilia Nur (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2020)
ABSTRACT Exclusive breastfeeding is pure breastfeeding, which is only given for 6 months without any additional liquid, which is needed for the growth process. Mothers who do not provide exclusive breastfeeding cause the child does not get appropriate nutrition. The purpose of this study was to determine the relationship of exclusive breastfeeding with stunting in children aged 3-5 years in Tambakrejo Village, Tambakrejo District, Bojonegoro Regency in 2019.This type of research is correlational analytic with cross sectional approach. Population Some mothers and children aged 3-5 years in Tambakrejo Village were 90 mothers and children aged 3-5 years, with a total sample of 73 mothers and children aged 3-5 years. Sampling using simple random sampling. Retrieval of data by questionnaire and observation then in editing, coding, scoring, tabulating, analyzed using the Chi Square statistical test.The results showed as many as 50 respondents who had received exclusive breastfeeding, the majority of which were 46 children aged 3-5 years (97.3%) having normal nutritional status. Of the two variables after being tested statistically using Chi Square obtained P Value= 0,000<a (0,05), so H0 is rejected, which means H1 is accepted, that is, there is a relationship between exclusive breastfeeding and stunting in children aged 3-5 years, with Contingensy Coeffisient 0.602 which means the level of closeness of the two relationships is strong.The conclusion in this study is the relationship between exclusive breastfeeding and the occurrence of stunting in children aged 3-5 years, it is expected that parents of respondents regularly visit the Posyandu to weigh their children so that if a health problem can be identified, give ASI to children aged 2 years. Key Words     :  Exclusive ASI, Stunting, Mother and Child 3-5 years old